Alih Kode dan Campur Kode Bahasa Makassar Dan Bahasa Indonesia pada Interaksi Siswa Sekolah Menengah Pertama - Andi Hariratul Jannah; Andi Fatimah; Sakinah Fitri (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to describe the form of code switching and code mixing in Makassar and Indonesian in the interaction of students at SMP 3 Takalar. This type of research is a qualitative approach with a qualitative research descriptive research design. The data in this study were oral data in the form of words, clauses, and sentences containing code-switching and code-mixing of Makassar and Indonesian languages originating from sources, namely class IX students of SMP Negeri 3 Takalar which were taken during a conversation process taking place between students. Data collection is done by recording, observing, and taking notes. The results of this study indicate that there are three forms of code switching in interaction between students at SMP Negeri 3 Takalar, namely occurring between sentences, occurring intra-sentence, and code switching on tags. There are two forms of code mixing, namely the insertion of elements in the form of words and phrases. Keywords: Code Switching, Code Mixing, Makassar Language, Indonesian Language.